Deteksi Dini Kanker Payudara (Ca Mamae) Dengan SADARI - Rukmawati, Sefrina (ABDIMAS Madani, 2026)
Breast cancer is the leading cause of death among women in Indonesia. Early detection through breast self-examination or BSE is a key factor in reducing mortality rates from breast cancer. This health education activity aims to improve the knowledge and skills of women of reproductive age in performing BSE. The education was conducted in [location], on [date] involving [number] participants of women of reproductive age. The methods used were lectures, discussions, demonstrations using breast phantom, and direct practice by participants. The education materials included understanding of breast cancer, risk factors, signs and symptoms, importance of BSE, proper timing for BSE, and correct BSE techniques. The results showed an increase in participants' knowledge by [x]% based on pre-test and post-test results, and [x]% of participants were able to practice BSE techniques correctly. It can be concluded that BSE education is effective in improving women's knowledge and skills in early detection of breast cancer. It is recommended to conduct ongoing education and mentoring activities so that women routinely perform BSE every month.